Digital Storytelling and Reading Comprehension in EFL Classrooms: A Systematic Literature Review - Nelvia Ibrahim (LPPM Institut Pendidikan Nusantara Global, 2026)
This article presents a Systematic Literature Review (SLR), a method for systematically identifying and synthesizing research, examining the use of digital storytelling (DST) – the creation of narratives using digital tools – to enhance reading comprehension (RC) among learners of English as a Foreign Language (EFL). Adopting the PRISMA 2020 protocol, an evidence-based guideline for reporting systematic reviews, the study analyzes 27 peer-reviewed articles indexed in Scopus, Web of Science, and ERIC, published between 2013 and 2026. The review is guided by three primary research questions: (1) Which DST platforms are most frequently utilized in EFL reading instruction? (2) To what extent is DST effective in improving reading comprehension across educational levels? and (3) What instructional approaches are employed in integrating DST into EFL reading practices? The findings indicate that DST consistently improves reading comprehension through mechanisms such as multimodal scaffolding, which supports learning across multiple modes like text, images, sound, and video; affective engagement, or learners' emotional involvement; and schema activation, the use of background knowledge to help learners understand texts. Frequently employed platforms include web-based applications, augmented reality tools, and collaborative online environments. Notably, 77.8% of the reviewed studies reported statistically significant improvements in reading comprehension in the experimental groups compared with the control groups. Furthermore, four dominant instructional approaches were identified: scaffolded multimodal reading (combining supportive tools and multiple content formats), collaborative story creation, retelling and response-based activities, and question-and-answer-oriented reading instruction. Despite these promising findings, several gaps remain, particularly in longitudinal research designs, studies situated in Southeast Asian contexts, and the development of explicit instructional design frameworks. The article concludes by outlining pedagogical implications for EFL practitioners and proposing directions for future research.